The effect of agency costs on the relationship between management characteristics and investment sensitivity to internal cash of companies listed on the Tehran Stock Exchange - Sedigheh Kamranrad; Seyed Hesam Vaghfi; Maliheh, Ghazvini (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: One of the topics that has been well discussed in the theoretical foundations of financial economics is the sensitivity of investment costs to cash flow. The degree of a firm's reliance on internal resources is determined by the sensitivity of investment to the firm's cash flow. In this regard, the present study examines the moderating role of agency costs on the relationship between CEO characteristics (including CEO optimism, ability, influence and experience) and investment sensitivity to firms' cash flows.Methodology: For this purpose, 136 manufacturing companies were selected from Tehran Stock Exchange through screening technique during 11 years (2011-2021). This research is a library and analytical-causal study based on panel data analysis; also, factor analysis was used to index CEO characteristics.Findings: The results showed that CEO optimism, ability, influence and experience have a significant effect on the sensitivities of firms' investment cash flows. In addition, the results showed that agency costs have a significant effect on the relationship between CEO optimism, experience, ability and influence and the sensitivities of firms' investment cash flows.Originality/Value: Improving our understanding in this area enables us to make optimal decisions in managing our investments in companies. This study helps us to gain deeper insights into the determinants of investing in companies and to select the most effective strategies for capital efficiency.